Five new species of Camelobaetidius Demoulin, 1966 (Ephemeroptera: Baetidae), and redescription of Camelobaetidius mexicanus (Traver & Edmunds, 1968) - Boldrini, R.; Pes, A. M.o. (Zootaxa, 2014)
The genus Camelobaetidius Demoulin, 1966 has 38 species distributed throughout the Neotropical Region, being one of the most studied genera of the family Baetidae. Based on material from Brazil, the aim of the present paper is to describe five new species of Camelobaetidius with the terminal filament as long as cerci, and to redescribe the nymph of C. mexicanus (Traver & Edmunds, 1968) based on a paratype from Mexico.